KAJIAN YURIDIS TENTANG DAMPAK PENGARUH IKLAN TERHADAP KONSUMEN - Pelupessy, Berd Elkiopas; Pelupessy, Sella Petrix (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The research, entitled "A Legal Study of the Impact of Advertising on Consumers," is motivated by the author’s experience purchasing substandard cosmetics due to the influence of advertising on electronic media (television broadcasts) and recent consumer complaints about inaccurate information conveyed in print media advertisements. The purpose of this study is to determine civil liability for consumer losses due to the influence of advertising. This is an empirical study that emphasizes field data; however, it begins with a review of secondary data obtained from the literature. The results reveal that the legal framework for print and electronic media advertising, as stipulated in Article 17 of Law No. 8 of 1999 and the Indonesian Advertising Code of Ethics, is ineffective in protecting consumers from the influence of advertising that uses excessively subjective opinions without supporting facts and is unprofessional. Therefore, it is necessary to immediately establish a Non-Governmental Consumer Protection Agency (NPPA) that can advocate for consumer interests. Government oversight of print and electronic media advertising is needed to ensure business actors are compliant and create a conducive business climate.